Pemanfaatan Pengetahuan Media Sosial (Online) untuk Edukasi Gizi Menarik dan Inovatif Terhadap Siswa Remaja SMA, SMK serta MA - Soeandi Malik Pratama; Azhari Umar Siregar; Linda Ernawati; Dara Keumala Chan; Nora Alisa Pulungan; Nurhidaya Fithriyah Nasution (Jurnal Kesehatan Amanah, 2024)
Social media has become one of the potential educational tools in improving adolescent nutritional knowledge. This study aims to analyze the use of social media as an interesting and innovative means of nutritional education for high school, vocational school, and Islamic high school students. The method used is a literature review of scientific articles obtained through databases such as Academia.edu, SpringerOpen, Google Scholar, and SINTA. The results of the analysis show that social media-based education, such as Instagram, Facebook and WhatsApp, can significantly improve adolescent knowledge about balanced nutrition. This increase occurs through creative approaches such as the use of videos, comics, and interactive games that can motivate adolescents to understand the importance of nutrition in everyday life. These findings emphasize the importance of utilizing social media as an effective educational tool to support positive behavioral changes related to nutrition in adolescents. Thus, social media-based education strategies can be an innovative step in facing the challenges of adolescent nutrition in the digital era.